Assessing the safety of bioactive ingredients in infant formula that affect the immune system: recommendations from an expert panel. Issue 2 (4th December 2021) - Callahan, Emily A; Chatila, Talal; Deckelbaum, Richard J; Field, Catherine J; Greer, Frank R; Hernell, Olle; Järvinen, Kirsi M; Kleinman, Ronald E; Milner, Joshua; Neu, Josef; Smolen, Kinga K; Wallingford, John C
ABSTRACT: Bioactive ingredients for infant formula have been sought to reduce disparities in health outcomes between breastfed and formula-fed infants. Traditional food safety methodologies have limited ability to assess some bioactive ingredients. It is difficult to assess the effects of nutrition on the infant immune system because of coincident developmental adaptations to birth, establishment of the microbiome and introduction to solid foods, and perinatal environmental factors. An expert panel was convened to review information on immune system development published since the 2004 Institute of Medicine report on evaluating the safety of new infant formula ingredients and to recommend measurements that demonstrate the safety of bioactive ingredients intended for that use. Panel members participated in a 2-d virtual symposium in November 2020 and in follow-up discussions throughout early 2021. Key topics included identification of immune system endpoints from nutritional intervention studies, effects of human milk feeding and human milk substances on infant health outcomes, ontologic development of the infant immune system, and microbial influences on tolerance. The panel explored how "nonnormal" conditions such as preterm birth, allergy, and genetic disorders could help define developmental immune markers for healthy term infants. With consideration of breastfed infants as a reference, ensuring proper control groups, and attention to numerous potential confounders, the panel recommended a set of standard clinical endpoints including growth, response to vaccination, infection and other adverse effects related to inflammation, and allergy and atopic diseases. It compiled a set of candidate markers to characterize stereotypical patterns of immune system development during infancy, but absence of reference ranges, variability in methods and populations, and unreliability of individual markers to predict disease prevented the panel from including many markers as safety endpoints. The panel's findings and recommendations are applicable for industry, regulatory, and academic settings, and will inform safety assessments for immunomodulatory ingredients in foods besides infant formula.